2022
DOI: 10.1038/s41598-022-06842-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel hepadnavirus in domestic dogs

Abstract: Hepadnaviruses have been identified in several animal species. The hepadnavirus prototype, human hepatitis B virus (HBV), is a major public health problem associated with chronic liver diseases and hepatocellular carcinoma. Recently, a novel hepadnavirus, similar to HBV, was identified in domestic cats. Since several pathogens can be shared between cats and dogs, we hypothesized that dogs could also harbor hepadnaviruses and we tested a collection of canine sera with multiple molecular strategies. Overall, hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…This survey revealed that 6.3% (40/635) of dog sera were DDH-positive (Diakoudi et al, 2022). Out of 40 DCH positive sera, only 23 samples have information related to hematological and serum biochemical assays which showed 47.8% (11/23) of DDH-positive dogs had an increased ALT (Diakoudi et al, 2022). This report proposes the possibility of inter-species transmission of hepadnavirus in carnivores.…”
Section: Italymentioning
confidence: 80%
See 2 more Smart Citations
“…This survey revealed that 6.3% (40/635) of dog sera were DDH-positive (Diakoudi et al, 2022). Out of 40 DCH positive sera, only 23 samples have information related to hematological and serum biochemical assays which showed 47.8% (11/23) of DDH-positive dogs had an increased ALT (Diakoudi et al, 2022). This report proposes the possibility of inter-species transmission of hepadnavirus in carnivores.…”
Section: Italymentioning
confidence: 80%
“…Interestingly, a novel hepadnavirus was also detected from dogs in 2022; it was tentatively named domestic dog hepadnavirus (DDH). The genome of DDH shared 98.0 and 96.9% nucleotide (nt) identity at the full genome level with Italian and Australian DCH, respectively (Diakoudi et al, 2022). This survey revealed that 6.3% (40/635) of dog sera were DDH-positive (Diakoudi et al, 2022).…”
Section: Italymentioning
confidence: 92%
See 1 more Smart Citation
“…Whether a pathogenic hepadnavirus infects domestic dogs is not known. HBV DNA was detected in 10% (19/189) of sera from wild domestic dogs in Brazil [ 16 ], and in Italy, sera from 40/635 dogs (6.3%) undergoing routine laboratory testing tested positive using a qPCR designed to detect DCH [ 17 ]. A complete genome of the dog-derived hepadnavirus shared 98% nucleotide homology with DCH, and a similarly high homology (97.7 to 98.7%) was found between canine-derived hepadnaviral sequences [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…HBV DNA was detected in 10% (19/189) of sera from wild domestic dogs in Brazil [ 16 ], and in Italy, sera from 40/635 dogs (6.3%) undergoing routine laboratory testing tested positive using a qPCR designed to detect DCH [ 17 ]. A complete genome of the dog-derived hepadnavirus shared 98% nucleotide homology with DCH, and a similarly high homology (97.7 to 98.7%) was found between canine-derived hepadnaviral sequences [ 17 ]. Evidence of an antibody response was also detected; 13/20 DCH qPCR positive canine sera tested positive for antibodies recognizing DCH core antigen on Western blot [ 17 ].…”
Section: Introductionmentioning
confidence: 99%